Pengaruh Kepemimpinan, Komitmen Organisasi, Dan Motivasi Terhadap Kinerja Guru Di Pondok Pesantren Mawaridussalam Deli Serdang - Andre M. Abdullah; Novita Enda Dewi Hasibuan; Ashari Ashari; Muhammad Yudha Nugraha; Gilang Perdana Kusuma; Supar Wasesa (Forum Kerjasama Pendidikan Tinggi, 2023)
The formulation of problem in this research how is influence of leadership on performance. How is influence of organization commitment on performance. How is influence of motivation on performance. How is influence of leadership, organization commitment and motivation on performance. The purpose of this research is for know influence and analize of leadership on performance. For know influence and analize of organization commitment on performance. For know influence and analize of motivation on performance. For know influence and analize of leadership, organization commitment and motivation on performance. The sample in this research is 60 employees, with data analysis technique used is descriptive analysis and multiple linear regression analysis. The research result is leadership variable influence positive and significant on performance. Organization commitment variable influence positive and significant on performance. Motivation variable influence positive and significant on performance. Leadership, organization commitment and motivation variable influence positive and significant on performance.